Ninth Five Year Plan 1997-2002 Volume-X Government of Assam - Planning Commission (Planning Commission, 1997)
Karbi Anglong is one of the Autonomous Hills district of Assam. Constituted under the 6th Schedule of the India Constitution. Now the district council has been renamed as Autonomous Council and more power has been delegated to it by the State Government and as such the Education upto college level has been entrusted at the disposal of the Council. The district is a backward one almost in all respects due to poor economic condition of the people/geographical barrier with poor comrnunication system and lack of general infrastructure. The total area of land of the district is 10434 Sq. K.M.s; which is nearly 13.20% of the total area of the State. The total population of the district is 6/62,723 and it comprise nearly 7.7% of the total population of the State of Assam.
Development Commissioner for Hill Areas